Development of Student Worksheets Based on Realistic Mathematics Learning Models to Improve Critical Thinking Skills for Class XI Vocational High School Students - Depari, Deliana Mayang; Syahlan; Matondang, Asnawati (Talenta Publisher, 2021)
This type of development research aims to determine the level of validity, effectiveness, and practicality of learning using Student Worksheets based on the Realistic Mathematics Learning model. This development uses the ADDIE development model that uses five stages: analysis, design, development, implementation, and Evaluation. The sample used is class XI SMK Private Mulia Medan. The results showed that the Student Worksheet, which was developed using the Realistic Mathematics Learning model, had a validity level of 4.6 with an outstanding category, the effectiveness level of the results of classical learning completeness in the first trial was 15% of the students completed while in the second trial. by 88% of students who completed. This shows an increase of 23% from the average critical thinking ability of students. Furthermore, the student response was very good with a percentage of 80%, and the practicality of the Student Worksheet obtained an average of 4.29 with a convenient category.